Stakeholders’ perspectives and experiences with the quality of essential medicines in primary healthcare facilities in Ghana: a qualitative study - Irene A. Kretchy; Gifty Sunkwa-Mills; Maxwell A. Antwi; Stanley K. Alor; Antoinette Squire; George Y. Afful; Tobias F. Rinke de Wit; Kwabena F. M. Opuni (Discover Public Health)
Abstract Background The availability of safe, effective, and affordable medicines indicates a quality health service and the achievement of a significant target area of universal health coverage. Health inequity in the global health system, due to socio-political factors like inadequate funding, weak regulatory frameworks, and limited resources, accounts for increased circulation of poor-quality medicines, especially in resource-limited settings, which could compromise the provision of safe and effective healthcare. This study explored the perspectives and experiences of key health sector stakeholders regarding strategies and barriers to ensuring the quality of essential medicines. Methods Thirty-four stakeholders comprising health facility administrators, pharmacy managers, healthcare providers, medicine manufacturers and distributors, and regulators were interviewed using face-to-face audio-recorded semi-structured interviews. Transcribed data were coded and analysed to generate themes relating to the study aim and organised into facilitators and barriers guided by the capability, opportunity, motivation and behaviour (COM-B) model. Results Most participants were males, 24 (70.6%), and between ages 36 and 45 (13, 41.2%). The barriers and facilitators to ensuring the quality of medicines were (1) physical and psychological capabilities (regulatory surveillance, inadequate financial and human resources, knowledge about medicines, attention to detail; (2) physical and social opportunities (technological support, institutional support, adequate storage facilities, health insurance support); and (3) reflective and automatic motivation (fear adverse effects of medicines, positive and negative client feedback). Conclusions The barriers and enablers underlying various stakeholders' perceptions and activities regarding ensuring quality medicines were identified, thus providing potential targets and strategies for future research and interventions to improve access to quality medicines in primary healthcare facilities.